Inorganic Chemistry 5th Edition - Housecroft, Catherine; Sharpe, Alan G. (Harlow: Pearson, 2018)
In its fifth edition, Housecroft & Sharpe's Inorganic Chemistry, continues to provide an engaging, clear and comprehensive introduction to core physical-inorganic principles. This widely respected and internationally renowned textbook introduces the descriptive chemistry of the elements and the role played by inorganic chemistry in our everyday lives. The stunning full-colour design has been further enhanced for this edition with an abundance of three-dimensional molecular and protein structures and photographs, bringing to life the world of inorganic chemistry. Updated with the latest research, this edition also includes coverage relating to the extended periodic table and new approaches to estimating lattice energies and to bonding classifications of organometallic compounds. A carefully developed pedagogical approach guides the reader through this fascinating subject with features designed to encourage thought and to help students consolidate their understanding and learn how to apply their understanding of key concepts within the real world.
Includes Appendix and index
Keywords: Inorganic chemistry; Chemical bonding; Transition metals